The Role of Teachers in Managing Negative Emotion (Aggressive) of Early Childhood - Nur Hazizah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
The current state of affairs in early childhood is the dominant type of aggressive emotion. Negative emotions (aggressive) can arise when the child is in school, so the teacher demands a role in managing the child's emotions. The purpose of writing this article is to find out the teacher's role in managing negative (aggressive) emotions in early childhood. The design of writing this article is a literature study. The teacher's role in managing negative emotions in children is to provide warmth to children, create comfort in school, reduce the level of frustration or pressure, use storytelling methods, role play, and sociodramas that use puppets in learning, give direction to aggressive children by speaking softly - slowly use positive sentences, and provide rewards for changing aggressive behavior.Keywords: Teacher's Role, Negative Emotions